Blood–Brain Barrier Breakdown: An Emerging Biomarker of Cognitive Impairment in Normal Aging and Dementia - Hussain, Basharat; Fang, Cheng; Chang, Junlei (Frontiers in Neuroscience, 2021)
Blood-brain barrier (BBB) plays a vital role in maintaining the specialized microenvironment of the neural tissue. It separates the peripheral circulatory system from the brain parenchyma, but facilitates them to communicate as well. Alterations in the distinct physiological properties of the BBB led to BBB breakdown associated with normal aging and various neurodegenerative diseases. In this review, we first briefly discussed the aging process, then reviewed the phenotypes and mechanisms of BBB breakdown associated with normal aging that further cause neurodegeneration and cognitive impairments. We also summarized dementia such as AD and vascular dementia, subsequently we discussed the phenotypes and mechanisms of BBB disruption in dementia correlated with cognition decline. Finally, we concluded that BBB breakdown can be used as an emerging biomarker in diagnosis of cognitive impairment associated with normal aging and dementia.